Noug Seed (Guizotia abyssinica) Cake Substituted with Dried Mulberry (Morus indica) and Vernonia amygdalina Mixed Leaves’ Meal on Growth Performances of Bonga Sheep at Teppi, Ethiopia - Gezahegn Mengistu; Getnet Assefa; Samuel Tilahun (Journal of Nutrition and Metabolism)
This study was conducted to evaluate noug seed (Guizotia abyssinica) cake substituted with dried mulberry and Vernonia mixed leaves’ meal on feed intake, body weight change, and digestibility of Bonga sheep fed on Rhodes grass hay at Teppi Agricultural Research Center, Ethiopia. The experiment was conducted using 25 yearling lambs with an average initial body weight of 20.83 ± 1.66 kg. Five lambs were allotted per treatment in randomized complete block design. Treatments were isonitrogenous supplements of 100% concentrate (49.5% NSC, 49.5% ground maize grain, and 1% salt) offered at 400 g DM/head/day (T1), 25, 50, 75, and 100 of NSC CP substituted by dried mulberry and Vernonia mixed leaves’ meal in T2 = 429.8 g/day, T3 = 459.5 g/day, T4 = 489.3 g/day, and T5 = 519 g/day, respectively. The sheep were fed Rhodes grass hay adlibitum and had free access to water and salt block. Intake and growth trail lasted for 90 days followed by 10 days of digestibility trial. The CP, NDF, and ADF contents of Rhodes grass hay were 7.9, 74.8, and 46.8 percent. The CP content of NSC, ground maize grain, dried mulberry, and Vernonia leaves was 32.4, 8.3, 18.5, and 22.5%, respectively. Total DM intake (g/day) was significantly higher for lambs in T3 (771.4) than in T1 (722.8) and T5 (642.8) but similar to T2 (754.9) and T4 (759.7). The CP intake was highest (P < 0.001) for sheep in T2 and T3, but lowest in T5. The apparent DM digestibility for T1 (70.8%), T2 (68.8%), and T3 (69.1%) was significantly higher than for T5 (64.4%), while T4 (67.9%) and T5 were not significantly different. The attained average daily gain (g/day) of sheep in T1 (87.7), T2 (82.0), T3 (83.4), and T4 (75.2) was higher (P < 0.01) than in T5 (56.0). The result of this study indicated that dried mulberry and Vernonia mixed leaves’ meal can substitute NSC as a protein supplement up to 75% inclusion level resulting in optimum DM and nutrient intakes and body weight gain of yearling Bonga sheep. This study also highlights the positive potential of dried mulberry and Vernonia mixed leaves’ meal as a supplement to ruminants on a basal diet of fibrous feeds.